Development of the method for identification of selected populations of torpedo scad, Megalaspis cordyla (Linnaeus, 1758), using microsatellite DNA analyses. CELFISH project – Part 4. (15th April 2017) - Kempter, Jolanta; Kielpinski, Maciej; Panicz, Remigiusz; Prüffer, Kaja; Keszka, Sławomir
Highlights: Torpedo scad is of high economic importance, where 20.000 tonnes are caught annually. Problems related with commercial substitution of species are observed. The SSR markers allowed the evaluation of the genetic structure of M. cordyla . Abstract: Catch and consumption of torpedo scad ( Megalaspis cordyla ) over the western Indian Ocean, but also the western Pacific from Japan to Australia is constantly increasing. Taking into account the degree of exploitation and missing information on the population structure of torpedo scad stocks it is crucial to provide population data. The analysis included individuals obtained in 2012 and 2013 from local markets in Madagascar, Tanzania, Vietnam and Cambodia and after successful DNA extraction fragment of the nuclear rhodopsin gene (RH1) and 9 microsatellite regions (SSRs) were amplified and analysed. Based on the obtained results it was found that there was no 100% overlap between the compared RH1 sequences and those from GenBank. In the case of the studied SSRs, the results allowed the initial characterisation and assessment of the genetic diversity of populations. Moreover, population assignment test distinguished the studied populations into two geographically distant subpopulations.